2021
DOI: 10.1111/jfpp.15522
|View full text |Cite
|
Sign up to set email alerts
|

The usage of Ohmic heating in milk evaporation and evaluation of electrical conductivity and performance analysis

Abstract: Milk production of World in 2018 was 683.217 thousand tons, while in Europe that this value was 220.377 thousand tons, and Turkey was reported that this was the value of 20.037 thousand tons (FAO, 2020). Especially during the production of technological products (yogurt, milk jam, etc.), the evaporation process is one of the most important methods applied to milk (Anandharamakrishnan, 2017;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…Therefore, more processing time negatively affects the average power value. Similarly, in the literature, average power values for pomegranate juice (Darvishi et al, 2013), cherry juice (Fadavi et al, 2020), tomato juice (Fadavi et al, 2018), verjuice (Cevik, 2021), milk (Ariç Sürme & Sabancı, 2021), and orange juice (Hwang et al, 2022) were positively affected by increasing voltage gradient (shortening of processing time). Similar trends were obtained in the present study.…”
Section: Resultsmentioning
confidence: 63%
“…Therefore, more processing time negatively affects the average power value. Similarly, in the literature, average power values for pomegranate juice (Darvishi et al, 2013), cherry juice (Fadavi et al, 2020), tomato juice (Fadavi et al, 2018), verjuice (Cevik, 2021), milk (Ariç Sürme & Sabancı, 2021), and orange juice (Hwang et al, 2022) were positively affected by increasing voltage gradient (shortening of processing time). Similar trends were obtained in the present study.…”
Section: Resultsmentioning
confidence: 63%
“…There are OH assisted evaporation applications of products such as cherry juice (Sabancı & Icier, 2020), pomegranate juice (Cokgezme et al, 2017), tomato paste (Torkian Boldaji et al, 2015). in the literature, and it has been reported in these studies that increasing voltage gradient positively affects the processing time so shortens the processing time (Ariç Sürme & Sabancı, 2021). In addition, it has been reported that the OH system shortens the processing time for thawing different vegetable purees (Tumpanuvatr & Jittanit, 2012), meat products (Cevik & Icier, 2021), and seafood (Rosnes et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Ohmic heating (OH), also known as "joule heating" and "electrical resistance heating," is the process of passing an alternating current through food between two electrodes. Thus, heat generation occurs in the product, and electrical energy is transformed into heat energy (Ariç Sürme and Sabancı, 2021;Rocha et al, 2022). It has been pointed out that this heating process provides a fast, efficient, and homogeneous heating process, especially for liquid foods (Alkanan et al, 2021;Ariç Sürme and Sabancı, 2021;Gavahian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, heat generation occurs in the product, and electrical energy is transformed into heat energy (Ariç Sürme and Sabancı, 2021;Rocha et al, 2022). It has been pointed out that this heating process provides a fast, efficient, and homogeneous heating process, especially for liquid foods (Alkanan et al, 2021;Ariç Sürme and Sabancı, 2021;Gavahian et al, 2019). The OH treatment has been applied in many foods for heating (Cappato et al, 2017), evaporation (Icier et al, 2017), drying (Acar et al, 2022), thawing (Cevik and Icier, 2021), cooking (Goksu et al, 2022), and extraction (Çilingir et al, 2021).…”
Section: Introductionmentioning
confidence: 99%